Role of Facility Management in Fire and Life Safety in Hospitals - Rohan Roy; Kuldeep Kumar; Virendra Kumar Paul (International Journal of Architectural Design and Planning, 2023)
Hospitals are significant buildings where people receive medical care around-the-clock. An internal hazard like a fire is more disruptive and puts more pressure on hospital authorities to ensure the safety of the patients and visitors who are unfamiliar building and the procedures to follow in case of a fire. In order to keep the patients safe in the event of a fire, every healthcare facility needs to have a plan in place. Building fire safety has become a major concern as a result of the fact that the current fire protection systems do not fully address all current fire hazards. Facility Management is beneficial in this instance. Through scheduled and periodic maintenance, facility management keeps places in good working order. The strategy used when providing services might range from offering entirely individualized services to offering services that are universally applicable. Each facility is reliant on the others, and each service is interdependent to each other. Standardization will place a focus on dependability, lowering defects, and saving costs within services. Numerous factors affect how well fire safety is managed, but the fundamental problem is that different services lack consistent procedures. This study proposes guidelines & recommendations that can be incorporated in the contractual obligations during the award of facility management services which can be instrumental for enhancing the fire and life safety of the building.
Keywords: Facility management; facility manager; fire & life safety; fire safety management; hospitals